FACTORS INFLUENCING INTENTION TO USE E-GOVERNMENT SERVICES AMONG STUDENTS IN UNIVERSITAS SEBELAS MARET, INDONESIA - Dwianto, Rahmad Agus; Darmawan, Arief Bakhtiar; Santoso, Joko; Pribadi, Ulung (Universitas Diponegoro, 2023)
This study aims to examine the factors that influence the intention of students to use e-government. The study used a survey method with 102 students as respondents from various study departments at Universitas Sebelas Maret, Indonesia, in 2021. The analysis was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the test R-square, path coefficients, outer loading, cross-loading, average variance extracted (AVE), Cronbach's alpha, and composite reliability. The results showed that students' desire to use or access e-government was positively and significantly influenced by students' trust in the government. Students trust to government is influenced by factors perceived usefulness, perceived ease of use, and security risk. The limitation of this research is that there is no analysis of the mediation test and moderation test.